Fair and Ethical Recruitment Berbasis Islamic Human Resource Management: Model Tata Kelola Pekerja Perikanan ILO C188 - Imron Natsir (Journal of Management and Creative Business, 2026)
Indonesia’s fisheries sector is central to employment, food security, coastal livelihoods, exports, and sustainable blue economy development. However, fisheries workers and fishing vessel crews remain vulnerable to unethical recruitment practices, including excessive recruitment fees, unclear contracts, information asymmetry, informal intermediaries, document retention, weak grievance channels, and limited social protection. This article aims to develop a Sharia-based Human Resource Management (HRM) governance framework to strengthen fair and ethical recruitment for fisheries workers. The study employs a qualitative conceptual approach, using a conceptual case study design, a systematic literature review, policy analysis, thematic synthesis, maqāṣid-based analysis, and HR governance mapping. The findings show that ethical recruitment in fisheries should be grounded in amanah, al-‘adl, ihsan, maslahah, contract transparency, zero recruitment fee, informed consent, grievance mechanisms, and compliance with ILO C188. Islamic Social Finance is positioned as a complementary compliance financing support for pre-work orientation, contract literacy, medical checks, emergency funds, grievance channels, and social protection for vulnerable workers. The novelty lies in integrating Islamic HRM, fair recruitment, ILO C188, maqāṣid al-syarī‘ah, decent work, ESG social-governance, and Islamic Social Finance into a Sharia-Based Fair and Ethical Recruitment Framework for Fisheries Workers.